INSTITUTIONAL AND INDIVIDUAL INVESTOR’S PREFERENCES IN THE CRUDE OIL AND NATURAL GAS BUSINESS CYCLE - Ayazi, Samad; Garkaz , Mansour; Saeedi , Parviz; Maetoofi , Alireza (Revista Inclusiones, 2019)
The main purpose of this paper is to test which firm’s characteristics attract institutional and individual investors in crude oil and natural gas Business cycle. The data about business cycle is obtained from statistics center of the Islamic Republic of Iran and the data about investment of investors, collected from explanatory notes to financial statements of 222 listed companies of the Tehran Stock Exchange during the years 2006 to 2015.This research is a purposeful, applied and methodological descriptive of correlation type. The present study is theoretically positive and inductive in terms of reasoning. The results of the research indicate that investor preferences in different industries are very important between institutional investors and individual investors, and institutional investors have a lower percentage of investment changes than individual investors. Also, the findings shown that the characteristics of the active industries in Iran have affected the preferences of institutional and individual investors in the in crude oil and natural gas business cycle. According to the findings, the crude oil and natural gas business cycle has experienced a recession in the years 2006 and 2012 through 2014 during the and there were boom in other years. The peak point is 2011 and the point perigee is 2012.